Promatics of Sexual Violence Based On The Direction of Government Policy In Handling It - Octasari, Poppy (Dinasti Research, 2024)
Cases of sexual violence are increasing from year to year, not only in Indonesia but also in several other countries, data from the National Commission for Women shows that cases of sexual violence continue to increase every year, as well as data from the Department of Justice , Office of Justice Program, Bureau of Justice Statistics, The National Crime Victims Survey shows a 68-second increase in Americans experiencing sexual assault. This shows that regulations regarding sexual violence are still weak. In Indonesia, even the Philippines, the Netherlands and the United States have regulated acts of sexual violence, but in substance it is still very lacking so that it has not been able to overcome the acts of sexual violence that have occurred so far. This study intends to analyze how the government should act in reducing the number of victims of sexual violence in Indonesia. Even though to date the government has issued laws and regulations related to sexual violence in 2022 which are issued through law, their implementation has not been optimal. Therefore, there is still a great need to improve government policy measures. Such as revising regulations relating to forms of sexual violence. Apart from that, the government must also be able to make derivative regulations for the Sexual Crimes Law so that they can be used legally.